Sectorial antennas for WSN localization system - Brás, Luís Pedro Marques (2014)
This work investigates low cost localization systems (LS) based on received signal strength (RSS) and integrated with different types of antennas with main emphasis on sectorial antennas. The last few years have witnessed an outstanding growth in wireless sensor networks (WSN). Among its various possible applications, the localization field became a major area of research. The localization techniques based on RSS are characterized by simplicity and low cost of integration. The integration of LS based on RSS and sectorial antennas (SA) was proven to provide an effective solution for reducing the number of required nodes of the networks and allows the combination of several techniques, such as RSS and angle of arrival (AoA). This PhD thesis focuses on studying techniques, antennas and protocols that best meet the needs of each LS with main focus on low cost systems based on RSS and AoA. Firstly there are studied localization techniques and system that best suit the requirements of the user and the antennas that are most appropriate according to the nature of the signal. In this step it is intended to provide a fundamental understanding of the undertaken work. Then the developed antennas are presented according to the following categories: sectorial and microstrip antennas. Two sectorial antennas are presented: a narrowband antenna operating at 2.4 to 2.5 GHz and a broadband antenna operating at 800MHz-2.4GHz. The low cost printed antennas were designed to operate at 5 GHz, which may be used for vehicular communication. After presenting the various antennas, several prototypes of indoor/outdoor LS are implemented and analyzed. Localization protocols are also proposed, one based on simplicity and low power, and the other on interoperability with different types of antennas and system requirements.